Road Crash Analysis and Countermeasures on Hilly Roads in a Developing Country Using Irap - Fernandez-Campusano, C (Taylor and Francis Ltd., 2025)
Road crashes are a major concern in the twenty-first century affecting the global economy and society in general. The earlier researcher used conventional methods such as statistical and GIS-based analysis to reduce road crashes with available road crash data. This research focuses on improvements needed in the existing road infrastructure of hilly roads to reduce the road crashes based on International road assessment programme (iRAP) which ranks the countermeasures needed to upgrade for reducing the road crashes in the existing roads. Thus helping to ensure the effective utilisation of available funds for road safety upgrades based on the ranking of countermeasures and implementing corrective measures in underdeveloped and developing countries roads based on the availability of funds. iRAP provides a straight forward and cost-effective technique to assess mitigation needs on hilly roads to reduce the road crashes. © 2025 Informa UK Limited, trading as Taylor & Francis Group.